Case Report: Kounis syndrome associated with urticaria following COVID-19 infection - Li, Xia; Cao, Ailin; Wang, Chengji; Guo, Qun; Chen, Xueying; Cui, Yinghua; Gu, Ying (Frontiers in Cardiovascular Medicine, 2025)
This case report describes a 58-year-old woman who sought treatment in the dermatology department after experiencing a three-day episode of widespread rash and itching, along with fever, chills, abdominal distress, and increased urinary frequency and urgency. Upon examination, she exhibited numerous erythematous patches and wheals on her face and body, devoid of blisters or erosions. Laboratory tests indicated an elevated white blood cell count, C-reactive protein, and serum amyloid A, while liver and kidney function tests were within normal limits. An electrocardiogram demonstrated sinus rhythm with T-wave alterations and a V2R/S ratio greater than 1. Subsequent nucleic acid testing confirmed the presence of COVID-19 infection, prompting the initiation of anti-allergic and supportive therapies. Despite this, the patient went on to develop chest pain, which was accompanied by electrocardiographic signs of acute extensive anterior wall myocardial infarction and elevated troponin I levels. Coronary angiography subsequently revealed mild coronary artery stenosis, with no significant blockages or stenoses in the coronary arteries, leading to a diagnosis of Kounis syndrome type II. This case underscores the significance of considering Kounis syndrome in patients with a history of infection or allergies who present with chest pain, emphasizing the necessity for thorough clinical evaluation and continued research.